FRASNIAN (UPPER DEVONIAN) BRACHIOPODS FROM ARMENIA: BIOSTRATIGRAPHIC AND PALAEOBIOGEOGRAPHIC IMPLICATIONS (Rivista italiana di Paleontologia e Stratigrafia, 2023)
An assemblage of seven brachiopod species belonging to the orders Rhynchonellida, Atrypida and Spiriferida are studied from three localities (Ertych, Djravank and Noravank) of Central Armenia. The examined material is recovered from shallow water nodular limestones and provides insights into the diversity of Frasnian brachiopods on that part of the northern margin of Gondwana preserved within the South Armenian Block. The revision of Atrypa (Planatrypa) ertichensis, a biostratigraphically significant species for the Frasnian of the Lesser Caucasus (Armenia and Nakhichevan), revealed the presence of frills, an ornamental feature rarely observed in Atrypa (Planatrypa) representatives and considered as unknown in this species. Taxonomic discussion also involves the selection of neotypes for Ripidiorhynchus gnishikensis and A. (P.) ertichensis. The newly described taxon, Angustisulcispirifer arakelyani n. gen., n. sp., appears to be one of the most biostratigraphically important species for the Frasnian of Armenia. The size variability of Cyphoterorhynchus koraghensis and Desquamatia (Seratrypa) abramianae is documented quantitatively for the first time and it shows a continuous and progressive growth without any distinct groupings; the former is a palaeobiogeographically important species for the Frasnian strata of the northern Gondwana margin. Pending the revision of the Pakistani and Iranian material ascribed to C. koraghensis, that may include several subspecies, a plaster cast of its lectotype from the Frasnian of Kuragh in Chitral (northwest Pakistan) and the holotype as well as one of the paratypes of Cyphoterorhynchus koraghensis interpositus from the Frasnian Bahram Formation of the Ozbak-Kuh region in eastern Iran are illustrated herein. Finally, a new Frasnian brachiopod zone, namely the Ripidiorhynchus gnishikensis–Angustisulcispirifer arakelyani assemblage Zone is here introduced for the studied sections. Although its base and top cannot be identified, it is constrained to the Frasnian based on conodonts identified in the Djravank section. It may be considered as a partly lateral equivalent of the Cyrtospirifer subarchiaci–Cyphoterorhynchus arpaensis brachiopod Zone established in Nakhichevan.